Damaged glyptodontid skulls from Late Pleistocene sites of northwestern Venezuela: evidence of hunting by humans? - Carlini, Alfredo Armando (2022)
The Muaco and Taima-Taima sites, in Falcón State of northwestern Venezuela, are among the earliest sites of human occupation in South America containing artifacts associated with preserved megafaunal remains and dating between 19,810 and 15,780 calybp. Here we report novel visual and CT scanning analysis of six glyptodont skulls of Glyptotherium cf. cylindricum from these sites, of which four exhibit distinct and similar patterns of breakages in the frontoparietal region that suggest intentional blows by direct percussion by humans, with fractures not being diagenetic but instead antemortem or transmortem. This hypothesized and unreported hunting technique focused in an area of the skull where the cephalic shield becomes thin, thus increasing the effectiveness of the blow. From Taima-Taima other glyptodont remains included an inverted carapace, also previously reported as probable evidence of human– glyptodont interaction during the latest Pleistocene. We estimated that roughly 150-170 Kg of potentially accessible muscles and fat of an adult Glyptotherium cylindricum could be used as food sources.